(untitled) (Bangladesh Journal of Animal Science, 2015)
The present study was conducted using records on four breeding bulls maintained at the Indrapuris Breeding and Forages Center (IBFC) of Aceh Cattle, Indrapuri district, Indonesia and 52 of their progeny born from 2010 to 2014 through natural mating. Family selection was practiced in this breeding station. Traits included in this study were birth weight at 0 day (BWc), weaning weight at 205 days of age (WWc), yearling weight at 365 days of age (YWc) and final weight at 550 days of age (FWc) of their progeny. The variance and covariance components were estimated by the Paternal Half-sib Correlation method with the Excel sheets of Microsoft office computer program. The mean body weights of the animals were BWc (13.25+1.18 kg), WWc (47.80+10.00 kg), YWc (73.97+16.79 kg) and FWc (101.87+23.91 kg). Estimated heritability (h2) for BWC was low (h2 < 0.10) and the other traits were high (h2>0.30). Higher standard error (SE) value than h2 caused by less number of calves observation. Research showed that best relative accuracy value (RA>1.00) reached in BWC. but its trait was not effective as selection criterion because of lower h2 value. It was concluded that WWC could be used as selection criterion for breeding bulls based on the similar estimated breeding value (EBV) rank and high h2 value. The EBV of WWC from breeding bull ID: 0752 was calculated and ranked accordingly. The EBVs of three top bulls ID were 100412 (10.32 kg), 100520 (9.38 kg) and 100317 (6.75 kg) and three top heifers were 100526 (9.65 kg), 100408 (7.04 kg) and 100807 (5.20 kg). It can be concluded that these top ranking three bulls and heifers can be selected and used in the breeding programs. Bang. J. Anim. Sci. 2015. 44(2): 85-91